PENINGKATAN PENDAPATAN KELUARGA MELALUI PEMANFAATAN PEKARANGAN RUMAH DENGAN MENGGUNAKAN TEKNIK VERTIKULTUR - Ati Kusmiati; Ummi Solikhah (Asian Journal of Innovation and Entrepreneurship, 2015)
Along with the increasing of population led to the conversion of agricultural land into residential. Urban settlements in the Tegalgede village especially in areas caused a high density of houses and each house has a narrow yard. Until now, the yard is not used optimally so that the views of the houses in the village seem barren. One cause of the narrowness of the land and yard is limited family income. Based on the condition and situation, the problem of community are: (1) The level of education and knowledge on verticulture techniques  is low, and (2) The level of education and knowledge about farming and marketing management are limited, and (3)People are not able to manage their yard optimally. Some approaches were used to solve the problem, such as socialization, counseling, and mentoring, demoplot on organic vegetable cultivation using verticulture technique, business management and marketing management. Results shows that: (1) housewife who are members of households in the group of Rose and Jasmine achieved education and new knowledge about how organic green mustard cultivation, management and cost analysis of farm business, (2) housewife has positive activities every day, (3) yard house become more green and lush, (4) Families can consume healthy organic vegetables and free of pesticides as well as save expenses, and (5) There is an additional income for housewives who sold organic green mustard (Brassica rapa) crops. Keywords: Verticulture, organic vegetable, business management, marketing management